2020
DOI: 10.1002/mp.13979
|View full text |Cite
|
Sign up to set email alerts
|

Geometric distortion characterization and correction for the 1.0 T Australian MRI‐linac system using an inverse electromagnetic method

Abstract: Purpose The magnetic resonance imaging (MRI)‐Linac system combines a MRI scanner and a linear accelerator (Linac) to realize real‐time localization and adaptive radiotherapy for tumors. Given that the Australian MRI‐Linac system has a 30‐cm diameter of spherical volume (DSV) with a shimmed homogeneity of ±4.05 parts per million (ppm), a gradient nonlinearity (GNL) of <5% can only be assured within 15 cm from the system's isocenter. GNL increases from the isocenter and escalates close to and outside of the edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…33 B 0 map results in each plane (2 × standard deviation of frequency shift) were as follows: axial plane (33 Hz), coronal plane (110 Hz), and sagittal plane (80 Hz), which showed that the largest distortion caused by the B 0 inhomogeneity was only half pixel in the ROI for the image acquisition protocol used here. 20 Two MR image sets scanned by the 1T MRI-Linac system were used to evaluate the performance of the proposed method. One set was acquired by scanning the phantom at various locations with turbo spin-echo (TSE) sequence, where no distortion corrections were implemented.…”
Section: A Data Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…33 B 0 map results in each plane (2 × standard deviation of frequency shift) were as follows: axial plane (33 Hz), coronal plane (110 Hz), and sagittal plane (80 Hz), which showed that the largest distortion caused by the B 0 inhomogeneity was only half pixel in the ROI for the image acquisition protocol used here. 20 Two MR image sets scanned by the 1T MRI-Linac system were used to evaluate the performance of the proposed method. One set was acquired by scanning the phantom at various locations with turbo spin-echo (TSE) sequence, where no distortion corrections were implemented.…”
Section: A Data Preparationmentioning
confidence: 99%
“…For any positions within the ROI, the GNL deviations can be calculated by the GNLNet. Based on the obtained GNL deviation information, a "GNL-encoding" reconstruction method developed in our previous studies was used to restore the undistorted image by the equation 20,29 :…”
Section: G Model Trainingmentioning
confidence: 99%
See 3 more Smart Citations